Demographic Determinants of Wastage Rate among Fresh Undergraduates in South-South Nigerian Public Universities - EDEKI, Oghomwen Mine; IDEHEN, Kate Ogheneruna (Ilorin Journal of Education, 2023)
This study investigated the demographic determinants of wastage rate among fresh undergraduates in South-South Nigerian public universities. The study was a descriptive survey that adopted the ex-post-facto research design. The population of the study comprised ten conventional universities in South-South Nigeria, one hundred and twelve (112) programmes in the universities and all the first-time undergraduates in the programmes.The sample consisted of 2676 fresh undergraduates from six programmes in two federal universities and two state government universities. Samples were purposively selected for the study. The research instrument was the checklist, titled “Student Enrolment and Flow Information Checklist” (SEAFIC). The instrument was validated by three experts in the Department of Educational Management, Faculty of Education, University of Benin, Benin City. Data gathered were analyzed using descriptive statistics. The findings revealed that: there were variations in the wastage rate among fresh undergraduates based on programmes, ownership of the university, generation of the university and gender. It was recommended among others, that university management should give more attention to variable of programme in allocation of learning facilities, adequate practical facilities should be provided for science programme to reduce the wastage rate among fresh undergraduates in the sciences and that state government should increase support to state universities to close the gap in variation in wastage rate between state and federal universities.